Inhibitory effect of interferon-beta on mouse spleen-derived mast cells - S. Konno; M. Adachi; K. Asano; K. Okamoto; T. Takahashi (Mediators of Inflammation)
Preparations of murine recombinant interferon (Mu-rIFN)-alpha, -beta and -gamma were assessed for their influence on in vitro growth of mast cells from normal mouse spleen cells (Sp C). Mast cell growth was inhibited by Mu-rIFNs when Sp C were exposed throughout the entire culture period to Mu-rIFNs. The most potent inhibitor of mast cell growth was Mu-rIFN-γ, followed by Mu-rIFN-β; Mu-rlFN-α had little effect. When added to IC-2 cells, clonal mast cell progenitor, both Mu-rlFN-β and −γ), significantly inhibited proliferative response of the target cells. The suppressive effect of Mu-rIFNs on IC-2 cells was selectively abolished by monoclonal antibodies against Mu-rIFN-β and −γ.